Thermal characterization and syngas production from the pyrolysis of biophysical dried and traditional thermal dried sewage sludge. (December 2015) - Han, Rong; Zhao, Chenxi; Liu, Jinwen; Chen, Aixia; Wang, Hongtao
Highlights: Thermal decomposition features of novel BDS bio-particle and traditional dried sludge. Pyrolysis kinetics simulation of BDS and TDS using pseudo multicomponent model. Different pyrolysis effects between BDS and TDS due to pre-biophysical adjustment. Fabricated BDS exhibited good properties for residue-derived energy by fast pyrolysis. Abstract: A novel method for energy recycling from sewage sludge was developed through biophysical drying coupled with fast pyrolysis. Thermal decomposition properties of biophysical-dried sludge (BDS) and thermal-dried sludge (TDS) were characterized through thermogravimetric (TG) coupled with mass spectrometry (MS) analysis. BDS exhibited typical peaks in each differential thermogravimetric (DTG) region and presented slower mass loss rates in H, C, and L regions (180–550 °C) but remarkable weight loss in region I (>550 °C) compared with TDS. The charring process centered at region I, was responsible for the prominent H2 emission from BDS. The pseudo multicomponent model showed that the Em values of BDS and TDS were 48.84 and 37.75 kJ/mol, respectively. Furthermore, fast pyrolysis of BDS was proven to facilitate syngas and char formation more than TDS. For the yielded syngas, the thermal conversion of BDS was characterized by high H2 and CH4 content beyond 700 °C.